2015
DOI: 10.1080/21532974.2014.991813
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Teachers in Integrating Digital Technology Into Language Arts Instruction to Promote Literacy

Abstract: A systematic review of relevant literature was conducted to provide a source of information and practical guidelines for teachers and teacher educators to consider instructional methods for using digital tools in elementary language arts classrooms to promote literacy. Focal studies are highlighted to provide rich descriptions of practical uses and considerations of integrating digital tools into literacy instruction. The following nine digital tools are discussed to provide methods, affordances, and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Several reviews used a descriptive 4 or statistical approach 5 to systematically search, filter, and classify the empirical studies related to the use of computer-assisted tools in supporting language learning. Colwell and Hutchison (2015) presented a systematic review of 11 empirical studies on digital tools used in K-5 language arts classrooms published between 2000 and 2013. The review suggested a variety of digital tools (e.g., blog, iPad apps, online games) could be used together in the classroom to support children’s reading comprehension, discussion and collaborative learning.…”
Section: Related Workmentioning
confidence: 99%
“…Several reviews used a descriptive 4 or statistical approach 5 to systematically search, filter, and classify the empirical studies related to the use of computer-assisted tools in supporting language learning. Colwell and Hutchison (2015) presented a systematic review of 11 empirical studies on digital tools used in K-5 language arts classrooms published between 2000 and 2013. The review suggested a variety of digital tools (e.g., blog, iPad apps, online games) could be used together in the classroom to support children’s reading comprehension, discussion and collaborative learning.…”
Section: Related Workmentioning
confidence: 99%
“…It is important to recognize that it can be complex for teachers to seamlessly incorporate digital technologies in classroom pedagogy (Shapley, Sheehan, Maloney, & Caranikas-Walker, 2010). Literacy teachers sense opportunities to connect students with digital technologies, yet teachers are not necessarily motivated to make this a routine experience (Colwell & Hutchison, 2015;Pytash, Ferdig, & Rasinski, 2013).…”
Section: Professional Concerns Messiness and Risksmentioning
confidence: 99%
“…Further, administrators may not be tech savvy, nor see more promise than problem in students' uses of technologies, and therefore may not encourage staff to foster classroom digital practices (Ertmer & Ottenbreit-Leftwich, 2010;Purcell et al, 2012). Lastly, it is a reality of teachers' daily lives that they have few minutes in the school day to learn, practice, or plan with new technologies, and few support staff may be available to coach (Colwell & Hutchison, 2015).…”
Section: Professional Concerns Messiness and Risksmentioning
confidence: 99%
See 2 more Smart Citations